ISLAMIC LAW INSTITUTIONALIZATION IN INDONESIA: AN ANALYSIS OF BUSTHANUL ARIFINS CONTRIBUTIONS - Mahabbati, Suci; Hardinal, Hardinal; Aunurrochim, Muhammad (Universitas Syiah Kuala, 2025)
This article explores the institutionalization of Islamic law in Indonesia, focusing on Busthanul Arifin's thoughts regarding the initiation of Religious Courts and the compilation of Islamic law within the Indonesian legal system. The study employs normative juridical methods, analyzing legal principles, concepts, and doctrines. The findings indicate that Busthanul Arifin's ideas have successfully contributed to the institutionalization of Islamic law in Indonesia through three main pillars: First, Islamic legal institutions, particularly Religious Courts, serve as the implementers of judicial authority, encompassing material aspects, authority, and legal apparatus; Second, laws and regulations, both material and formal, embody the spirit of sharia (al-Qur'an and hadith), forming the basis for jurisprudence and guiding judicial decision-making; third, the legal consciousness of Islamic law transforms it from an abstract concept into a tangible, living law, referred to as